PELANGGARAN ETIKA BISNIS PT ASURANSI JIWASRAYA PERSPEKTIF NAQUIB AL-ATTAS - Riza, Ira Febriliana Dewi; Rosyidah, Rihadatul Izza; Syaifuddin, Helmi (HUMAN FALAH: Jurnal Ekonomi dan Bisnis Islam, 2024)
Islam holds all aspects of human life, including muamalah (business). Through revelation (the Qur'an and hadith), Islam establishes a set of rules that must be obeyed in muamalah activities, known as Islamic business ethics. Islamic business ethics is ethical business behaviour based on the Qur'an and the hadith of the Prophet Muhammad. This research aims to analyze business ethics violations committed by the Jiwasraya Insurance Company from the perspective of Syed Muhammad Naquib Al-Attas, a Muslim scholar famous for his ethical concepts based on the Islamic worldview. In 2018, the Jiwasraya Company announced a defeat to pay claims on unpaid policy from JS Saving Plan product customers amounting to 802 Billion rupiahs until the end of 2019, with a mega scandal that shocked Indonesia. This research uses a descriptive qualitative method sourced from secondary data from the works of Naquib Al-Attas, news, and information related to business ethics violations at the Jiwasraya Insurance Company and various literature appropriate to the research matter. The results of this research show that there has been a violation of business ethics, which causes the company to be incapable of paying policy claims, and several solutions are offered from Naquib Al-Attas' perspective.